Pengaruh Penggunaan Alat Modifikasi Pipa Aluminium Terhadap Kemampuan Lempar Lembing pada Siswa SMA Negeri 1 Setu Kabupaten Bekasi - Windary Windary; Dhika Bayu Mahardhika; Rhama Nurwansyah Sumarsono; Asep Suherman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aimed to determine the effect of using an aluminum pipe modification tool on students' javelin-throwing abilities. This research design uses Pretest-Posttest Control Group Design. The sampling technique used in this study was purposive. The sample in the study was students of class IPA 4 who were divided into two groups (experimental group and control group), with 18 students in each group. The experimental group was given treatment using aluminum pipe modification tools, while the control group was not assigned treatment and aluminum pipe modification tools. Data collection techniques used include a pre-test and post-test. It was analyzed using an independent t-test. From the results of the t-test calculation, the results of Sig. of 0.000 where if Sig. <0.05, then there is a significant difference. Then the results of the t-test obtained tcount of 4.127 where if tcount 4.127 > ttable 2.021 (df 34), then it is declared a significant difference. In conclusion, the use of a modified aluminum pipe has an increasing and significant effect on the javelin-throwing ability of the students of SMA Negeri 1 Setu, Bekasi Regency. Keywords: Ability, Aluminum Pipe Modification Tool, Javelin Throw.